Variable-interval schedules of timeout from avoidance: effects of chlordiazepoxide, CGS 8216, morphine, and naltrexone. - Galizio, M (1987)
Rats were trained on concurrent schedules in which pressing one lever postponed shock and pressing the other occasionally (variable-interval schedule) produced a 2-min timeout during which the shock-postponement schedule was suspended and its correlated stimuli were removed. These procedures provided a baseline for studying the effects of drugs on behavior maintained by different sources of negative reinforcement (shock avoidance and timeout from avoidance). Experiment 1 studied a benzodiazepine agonist, chlordiazepoxide, and antagonist, CGS 8216. Chlordiazepoxide (2.5-30 mg/kg) had little effect on avoidance responding except at higher doses, when it reduced responding. By comparison, responding on the timeout lever was increased in 5 of 6 rats. These effects were reversed by CGS 8216 (2.5-5 mg/kg) in the 2 rats tested, but CGS 8216 had no effect by itself. Experiment 2 studied an opiate agonist, morphine, and antagonist, naltrexone, with 3 rats. Morphine's (2.5-20 mg/kg) effects were opposite those of chlordiazepoxide: At doses that either increased or had no effect on avoidance responding, morphine depressed timeout responding. Naltrexone (5 mg/kg) reversed these actions but had no effect by itself.